2021
DOI: 10.3390/molecules26123480
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bioaccessibility of Bioactive Compounds from Citrus Pomaces and Orange Pomace Biscuits

Abstract: The present investigation aimed to provide novel information on the chemical composition and in vitro bioaccessibility of bioactive compounds from raw citrus pomaces (mandarin varieties Clemenule and Ortanique and orange varieties Navel and Valencia). The effects of the baking process on their bioaccessibility was also assessed. Samples of pomaces and biscuits containing them as an ingredient were digested, mimicking the human enzymatic oral gastrointestinal digestion process, and the composition of the digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…Wang et al reported that orange extracts with high amount of hesperidin prolonged the mean lifespan of worms by 26.4%, suggesting that hesperidin may be the main contributor in lifespan extension of the extracts 15 . Nobiletin, a main flavonoid in mandarin pomaces, 41 enhanced the mean lifespan by 21% and also exhibits beneficial effects on aging‐related functional declines. And the 50 μM of naringin can remarkably prolong the mean lifespan of C. elegans by 17.30% 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that orange extracts with high amount of hesperidin prolonged the mean lifespan of worms by 26.4%, suggesting that hesperidin may be the main contributor in lifespan extension of the extracts 15 . Nobiletin, a main flavonoid in mandarin pomaces, 41 enhanced the mean lifespan by 21% and also exhibits beneficial effects on aging‐related functional declines. And the 50 μM of naringin can remarkably prolong the mean lifespan of C. elegans by 17.30% 42 .…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the amelioration of intracellular formation of Reactive Oxygen Species (ROS) by TGS yogurt digest three cell lines were employed: IEC-6 (normal rat small intestine epithelial cells), CCD-18Co (normal human colon fibroblast cells) and RAW264.7 (mouse macrophages) cells. The assays were carried out as described by Fernández-Fernández et al [ 25 ]. The tests were carried out by seeding 20,000 IEC-6, 10,000 CCD-18Co and 80,000 RAW264.7 cells/well in sterile 96-well plates and incubating for 24 h reaching cell confluence.…”
Section: Methodsmentioning
confidence: 99%
“…According to Fernández et al ( 40 ), the phenolic content of mandarin pomace ranged from 6.6 to 11.0 mg GAE/g, whereas grapefruit, orange, and lemon peels had high phenolic content, i.e., 77.3, 49.8, and 35.6 mg of GAE/g, respectively, with a moderate antioxidant activity ranging from 73 to 75% ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Montenegro-Landvar et al ( 45 ) that aqueous extract of orange waste might be a substantial source of 4-hydroxybenzoic acid and hesperidin. The flavonoid contents in the citrus pomace's methanolic extract showed nobiletin, hesperidin/neo-hesperidin, tangerine, heptamethoxyflavone, tetramethyl scutellarin, and naringin/narirutin were detected by UHPLC-MS/MS ( 40 ).…”
Section: Resultsmentioning
confidence: 99%